3x+24=12x
adding -3x
24=9x
dividing y 9
x=24/9
=8/3
=2 2/3
2007-01-05 02:36:26
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
3/2 (x+8) = 6x
     x+8 = â
à 6x
     x+8 = 4x
   4x - x = 8
      3x = 8
       x = 8/3
        = 2â
i may've read ur equation in the wrong way, here if the equation is something else like this
   3
————— = 6x
2 ( x + 8 )
       3 = 6x { 2 ( x + 8 ) }
       3 = 6x ( 2x + 16 )
       3 = 12x² + 96x
       0 = 12x² + 96x - 3
       0 = 4x² + 32x - 1
       0 = x² + 8x - ¼
       0 = x² + 8x + 16 - 16 - ¼
   16 + ¼ = x² + 8x + 16
     65/4 = ( x + 4 )²
            ____
    x + 4 = ±â65/4
              ____
       x = -4 ± â65/4
hence,
x = 0.03113 or x = -8.03113
2007-01-05 02:43:25
·
answer #2
·
answered by xyeslam 3
·
0⤊
0⤋
3/2 (x+8) = 6x simplify
3X+24/2=6x multiply each side by 2
3X+24=12X move x values to one side
24=9X divide each side by 9
x=24/9 reduce the fraction
x=8/3
x=2 2/3
2007-01-05 02:35:03
·
answer #3
·
answered by Blunt Honesty 7
·
1⤊
0⤋
3/2(x + 8) = 6x
2[3/2 (x + 8)} = 2(6x)
3(x + 8) = 12x
3x + 24 = 12 x
3x + 24 - 3x = 12x - 3x
24 = 9x
24/9 = 9x/9
24/9 = x
8/3 = x
2 2/3 = x
- - - - - s-
2007-01-05 07:57:44
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
0⤋
1. distribute
3x/2 + 12 = 6x
2. multiply everything by 2 to get rid of the fraction
3x + 24 = 12x
3. subtract 3x from both sides
24 = 9x
4. divide both sides by 9
24/9 = x
5. reduce by dividing by a common factor (3)
x = 8/3
2007-01-05 02:36:56
·
answer #5
·
answered by Philippe 3
·
1⤊
0⤋
3/2(x +8) =6x
3(x+8) = 2(6x) =12x Multipy across the board by 2
3x +24 = 12x
24 = 12x -3x
24 =9x
24/9 =x
Therefore x=2.666666
2007-01-05 02:38:45
·
answer #6
·
answered by Aine 3
·
0⤊
0⤋
It almost certainly means that you should do your own homework.
Is this 3 over 2(x+8) or 3/2 times (x+8)?
2007-01-05 02:42:06
·
answer #7
·
answered by Chris H 3
·
1⤊
0⤋
3/2(x+8) = 6x
Take the 2 frm the denominator to the RHS
3(x+8)= 2*6x
3x+24=12x
24=12x-3x
24=9x
24/9=x
therefore when simplified x=8/3
hope that helps!
(hmm it cud be how xyeslam has shown it above...the 2nd method i mean)
2007-01-05 02:44:17
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
Please re-check the problem to make sure you typed it correct > is it (3/2)(x+8) = 6x Or [3/2(x+8)] = 6x?
2007-01-05 08:53:26
·
answer #9
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
3/2(x+8)=6x
x+8=6x(2/3)
X+8=4x
3x=8
x=8/3
2007-01-05 02:40:16
·
answer #10
·
answered by Sony 1
·
0⤊
0⤋